2010
DOI: 10.1093/sw/55.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Considerations for Social Service Agencies Working with Muslim Clients

Abstract: Social service agencies and practitioners are continually challenged to provide services that are effective for, and reflective of, cultural and religious diversity. Qualitative interviews were conducted with 50 social work practitioners in four Canadian cities to gain insight into methods of practice that are culturally sensitive for work with Muslim clients. No hard-and-fast rules are identified, but the findings point to some cultural values and issues to consider (in particular the roles of faith and spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Movies like Mooz‐lum (Peace Film & Basir, ) and agencies such as Inner‐City Muslim Action Network (http://www.imancentral.org), CAIR (http://www.cair.com), and the Islamic Society of North America (http://www.isna.net) serve as a useful starting point for any counselor. Although counselors may seek to gain knowledge outside of the client–counselor interaction process, researchers have suggested that an approach that allows the client to be the expert and the counselor the learner is beneficial when a counselor is working with Muslim Americans (Cashwell & Young, ; Graham, Bradshaw, & Trew, ).…”
Section: Implications For Treatment Of African American Muslimsmentioning
confidence: 99%
“…Movies like Mooz‐lum (Peace Film & Basir, ) and agencies such as Inner‐City Muslim Action Network (http://www.imancentral.org), CAIR (http://www.cair.com), and the Islamic Society of North America (http://www.isna.net) serve as a useful starting point for any counselor. Although counselors may seek to gain knowledge outside of the client–counselor interaction process, researchers have suggested that an approach that allows the client to be the expert and the counselor the learner is beneficial when a counselor is working with Muslim Americans (Cashwell & Young, ; Graham, Bradshaw, & Trew, ).…”
Section: Implications For Treatment Of African American Muslimsmentioning
confidence: 99%
“…Therefore, adoption of broad frameworks of cultural sensitivity is imperative. Culture undergoes change as it intersects with all variables of gender, race, geography, race and class (Graham, Bradshaw, and Trew, 2010). In modern social work a void of a great nature exists as attempts to locate both religion and spirituality within the framework of social work are nascent and apologetic.…”
Section: Beginning With a Cultural Approachmentioning
confidence: 99%
“…Literature on social work with Muslims has expanded over the past 10 years (Graham et al 2010 ;Hodge 2005 ;Hodge and Nadir 2008 ;Nadir 2003 ), but in general little content on Islam is included in social work education Hodge and Nadir 2008 ). Clinical practice guidance in particular has been lacking.…”
Section: Muslim Clients: Orientation For the Relational Social Workermentioning
confidence: 99%
“…Most of what practitioners do know is based on media stereotypes of Islam and Muslims. As relational clinical practitioners, it is important to become familiar with the worldview of the Muslim client in order to understand the role the client's faith plays in his or her life, as well as in the resolution of the challenges he or she may be facing (Graham et al 2010 ).…”
Section: Muslim Clients: Orientation For the Relational Social Workermentioning
confidence: 99%
See 1 more Smart Citation